Inovaç\~ao tecnológica e sustentabilidade da cadeia de produç\~ao: Um exercício para a água no Brasil - Jaqueline Coelho Visentin; Leonardo Szigethy (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– Technological innovation is considered an increasingly important factor for the sustainable use of natural resources. With technology, it may be possible to maintain the quantity produced of a given good by reducing pressure on the environment. However, the gain in efficiency in the direct use of natural resources does not necessarily mean a significant reduction in this pressure. To achieve this goal, it is necessary to be inserted in a sustainable production chain. That is, the efficiency gain must not only occur in the direct use of these resources, but also in the volume of natural resources needed to input used in this good production, the so-called indirect use. The objectives of this paper are to map the use of water along the supply chain in Brazil and to estimate the impacts of adopting less water-intensive technologies on total water intensity and water withdrawal. For this, the national input-output model was used for the year 2017. These impacts were estimated based on the hypothesis of the adoption of less water-intensive technologies by agriculture, industry and sanitation. Among the main results, it is highlighted that a considerable part of the total water intensity of economic activities refers to indirect intensity and the adoption of more efficient technologies in the use of water by some economic activities has the potential to reduce the total water intensity of other activities and to change the participation of different final consumers in the demand for embedded water in goods and services.
Keywords: Q25; R15; Q55; 330; technology; water; input-output model